RANCANG BANGUN SISTEM INFORMASI OPEN JOURNAL SYSTEMS (OJS) ANDROMEDA PADA PRODI MANAJEMEN BISNIS SYARIAH IAIN PONTIANAK - Julianto; Diandra Chika Fransisca (LPPM UNIVERSITAS BINA INSAN, 2026)
Open Journal Systems (OJS) is an open-source software application for managing and publishing peer-reviewed online scientific journals developed by the Public Knowledge Project (PKP) and released under the GNU General Public License. This study aims to design and implement OJS Andromeda to support the management of scientific publications in the Sharia Business Management Study Program at IAIN Pontianak. The method used is system implementation with the stages of needs analysis, system design using Unified Modeling Language (UML), PKP-based OJS implementation, journal workflow configuration, and testing using Black Box Testing. The results show that the system design has been adapted to the needs of five user actors through Use Case Diagrams and Activity Diagrams. All main features tested, including Login, New Submission, Review Form, Create Issue, and Publish Article, were declared Valid. The presence of OJS Andromeda provides benefits in the form of a more structured division of journal management work and a wider publication reach because it can be accessed online and has the potential to be indexed in Google Scholar, DOAJ, and Garuda.